Adaptive Security Architectures for Global Sensing Applications - Schreckling, Daniel; Posegga, Joachim (Electronic Communications of the EASST, 2011)
We discuss the problem of providing a security architecture for global sensing applications which are distributed in nature and which allow for a variety of different sensing tasks. We propose to make use of data security policies tagged to data or resources generating, processing, or consuming data on a sensing device. These policies are used to feed an automated information flow analysis process which identifies unsatisfied security constraints. Results of this analysis are used to automatically adjust an application to comply with the given security constraints.